Kelestarian Perusahaan Batik Dan Pengaruh Budaya Terhadap Pembangunan Komuniti Di Kampung Batik Laweyan Surakarta, Indonesia - Sarjiyanto, Sarjiyanto (2021)
This study aims to identify and analyse the sustainability factors of the batik industry in Kampung Batik Laweyan (KBL), Surakarta and the way these factors relate and shape successful local community development. Data collection was administered through a survey questionnaire involving 510 respondents that comprised 254 enterprises and 256 community members selected through stratified random sampling techniques. The findings show that all factors of industrial sustainability, namely: industrial economic factors, industrial environmental factors, and industrial social factors have a positive and significant relationship to the sustainability of the batik industry. The sustainability of the batik enterprise indicated a positive and significant relationship to the well-being of the community and social capital. This study also proved that the influence of enterprises’ sustainability on social capital was highly influenced by culture. This however cannot be proved when culture was linked to the relationship between enterprises sustainability and community well-being. Overall, this study concludes that the way sustainability of the batik industry in KBL contributes towards community development was also influenced by local cultural factors, particularly the social capital of the community